392 Basic Researcher Interviews to iDentify Gaps to Enabling Translation (BRIDGE Translation) - Parisorn Thepmankorn; Barbara Tafuto; Anthony Gonzalez; Farah Anwar; CÃ©line Gelinas; Nancy Fiedler (Journal of Clinical and Translational Science, 2023)
OBJECTIVES/GOALS: Despite expanded interest in translational research, barriers in funding, infrastructure, staffing, training opportunities, and interdisciplinary collaboration still remain. Our goal was to interview basic science researchers to identify research barriers and potential areas for improvement. METHODS/STUDY POPULATION: After receiving an IRB determination for a quality improvement study, 15 New Jersey-based principal investigators (PIs) from various departments and at various stages of their careers were virtually interviewed one-on-one by a trained medical student and asked a series of standardized questions about their subjective experiences with their institutions’ research processes, training and mentoring, interdisciplinary collaboration, and intellectual property. The interview was then transcribed to complete an anonymous, standardized REDCap form. Qualitative data analysis was performed to identify common themes, barriers, and gaps in conducting translational research as reported by the PIs. RESULTS/ANTICIPATED RESULTS: Of the 15 PIs, 4 (27%) were assistant professors, 6 (40%) associate professors, and 5 (33%) professors. 5 (33%) joined the institution less than 5 years ago. The most common barrier was translational research funding. Time needed to navigate administrative and regulatory processes and access to clinical collaborators were other common barriers. One PI noted leaving the institution due to difficulty accessing clinicians and patient samples. PIs with extensive training or who reported successfully conducting translational research noted fewer barriers. Suggested solutions included programs and grants to link basic scientists with clinicians, a streamlined IRB process, and better staffing to support research. DISCUSSION/SIGNIFICANCE: The findings suggest a need to increase grant funding for translational research. Improving support staffing and minimizing administrative barriers would also be helpful. Improving the dissemination of available resources, grants, and guidance on administrative processes may further decrease barriers.